Islamic Education Management in Improving the Quality of Educational Institutions - Muh. Idris (Rahis Cendekia Indonesia, 2025)
The improvement of educational quality has become a major priority for educational institutions in response to increasing global competition, rapid social change, and rising public expectations. Educational institutions are required not only to deliver academic knowledge but also to implement effective management systems that ensure efficiency, accountability, and continuous improvement. In the context of Islamic educational institutions, such as madrasahs, Islamic schools, and pesantren, quality improvement must be achieved while preserving Islamic values and institutional identity. Therefore, Islamic education management plays a strategic role in integrating professional management practices with Islamic principles to enhance institutional performance and sustainability. This study aims to analyze the role of Islamic education management in improving the quality of educational institutions through a comprehensive review of relevant literature. The research employed a qualitative approach using a library research (literature review) design. Data were collected from primary and secondary sources, including books, peer-reviewed journal articles, research reports, and official documents related to educational management, quality assurance, and Islamic education. The collected data were analyzed using descriptive-analytical techniques by identifying key management functions, strategies, and themes that contribute to quality improvement in Islamic educational institutions. The findings indicate that effective Islamic education management significantly contributes to institutional quality through the implementation of core management functions, including strategic planning, leadership, human resource development, resource management, and continuous evaluation. Strategic planning aligned with institutional vision, mission, and Islamic values provides clear direction and coherence in educational programs. Leadership grounded in ethical and spiritual principles fosters professionalism, motivation, and commitment among educators and staff. In addition, effective management of human resources, facilities, and finances supports a conducive learning environment and enhances institutional credibility. Continuous evaluation and quality assurance mechanisms enable institutions to monitor performance, identify weaknesses, and implement improvements in both academic achievement and character development. However, the study also reveals several challenges faced by Islamic educational institutions, such as limited management capacity, insufficient professional development, and difficulties in adapting modern management practices to traditional institutional cultures. These challenges highlight the need for capacity building, leadership training, and the adoption of innovative management approaches without compromising Islamic values.n conclusion, the study affirms that Islamic education management is a key factor in improving the quality and sustainability of educational institutions.